Strategi Pemberdayaan Perempuan dalam Masyarakat Islam: Studi Wacana Kritis Pemikiran Fatima Mernissi dalam Buku Beyond The Veil - Rofifah; Asep Shodiqin; Enok Risdayah (Tamkin: Jurnal Pengembangan Masyarakat Islam, 2025)
This research aims to explore and analyze women's empowerment strategies in Islamic societies through a critical discourse approach, focusing on the thoughts of Fatima Mernissi in her book entitled Beyond The Veil. Fatima Mernissi, a leading thinker and academic in gender and Islamic studies, offers a critical and innovative perspective on the position of women in traditional Islamic society. This research adopts critical discourse analysis methods to assess how Mernissi constructs her arguments and empowerment strategies, as well as the impact of her thinking on social change in an Islamic context. This research uses a qualitative approach by analyzing the text of the book Beyond The Veil in depth. The main focus is on Mernissi's understanding of the social constraints Muslim women face and the strategies she proposes to overcome these barriers. The results of the analysis show that Mernissi emphasizes the importance of reinterpreting religious texts, education, and the active involvement of women in public life as keys to empowerment. She criticizes patriarchal structures that inhibit women's participation and encourages the creation of new spaces for women to actualize their potential. This study finds that Mernissi's thinking not only provides a sharp critique of gender inequality in Islamic society, but also offers concrete solutions rooted in Islamic values. Islamic values themselves. The recommendations she provides for social and educational reform can provide important guidance for women's empowerment efforts in the contemporary context. It is hoped that this research will contribute to a better understanding of women's empowerment strategies in Islamic societies and pave the way for further studies on the role of women in social change.